PENGARUH PEMBERIAN REBUSAN EDAMAME (KACANG KEDELAI) TERHADAP PRODUKSI ASI PADA IBU NIFAS DI PUSKESMAS RANTAU LABAN KOTA TEBING TINGGI - Selvia Yolanda Dalimunthe, Endang Sihaloho, Mery Krista Simamora (JURNAL PIONIR, 2022)
ASI ) is the best investment for health and intelligence of children. One of the causes of low exclusive breast feeding is low nutritional intake and insufficient amount of breast milk produced to meet the baby’s demand. Vegetable soybeans, known ad Edamame have the potential for nutrition for breast feeding mothers, because they contain phytosterol compounds that function to increase and accelerate milk production ( lactogogum effect ). The purpose of this study was determine the effect of Edamame on milk production in postpartum mothers at the Rantau Laban Health Center, Tebing Tinggi City. The research method used was an experiment with a one group pretest posttest approach. The reasearch sample was 15 postpartum mothers. Sampling using is total sampling technique. Giving Edamame as much as 65 grams/day for 5 days. bivariate analysis using the wilcoxon statistical test, the result showed p value = 0.000 which is smaller than 0.05 so that there is an effect of giving Edamame on breast milk production in postpartum mothers at the Rantau Laban Community Health Center, Tebing Tinggi City. Suggestions for health assignment are expected to provide proper nutrition to postpartum mothers while breast feeding so that they can support the success of goverment programs in efforts to increase the coverage of exclusive breast feeding. Keywords : Edamame ( Soybean ), Breast Milk Production, Post Partum.